West meets Islam in contemporary world - construction project leadership perspective - Senam, Muhamad Rosdi; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Mohd Zaini, Rapiah (American Research Institute for Policy Development, 2015)
Project management is a combination of both science and art as the merger of the terms of ‘project’ reflects to the technical knowledge, skills and competencies and ‘management’ refers to the human related components such interpersonal and leadership capabilities. Leadership is identified as central and core to successful business outcomes and prevails as crucial in any group or collective tasks. Project management is a business and an organisation, and the need to have an effective project leadership in place at all project phases is salient to ensure successful project outcomes, that fulfills project objectives as well as adhering to the objectives from the lens of Islam; to seek the pleasure of Allah (Mardhatillah)and His reward and eventually to achieve success in this world and in the Hereafter. With the increasing leadership challenges in leading construction projects nowadays, as complexity, stakeholders’ requirements and project failure grows,as well as continuous ethical issues and malpractices, project management awaits divine guidance that has its sources from and accord to the principles and values as prescribed in the Qur’an and the Sunnah. This paper aims to highlight, compare and discuss the Western modern perspective of project leadership with the one from the proposed Islamic perspective and also attempts to demonstrate some points on the merits of imbuting Islamic principles of leadership into projects.